2021
DOI: 10.1186/s12889-020-09789-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased cold injuries and the effect of body mass index in patients with peripheral vascular disease

Abstract: Background Exposure to extremely or moderate low temperatures is associated with increased morbidity and mortality risk. Peripheral vascular disease (PVD) is a slow and progressive circulation disorder. Given that cold temperature causes constriction of the small arteries and veins in the skin, patients who suffer from peripheral circulation problems, like PVD, may be vulnerable to cold injuries. This study aimed to investigate the association between PVD and cold-induced injuries in the winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
6
0
3
Order By: Relevance
“…The above discussion clarifies the reason for the significant increase in tourist arrivals at hot springs when environmental temperature decreases. From a biological perspective, possible pathways linking exposure to a low-temperature environment with human discomfort may involve organ injuries caused by a decrease in the core body temperature (Min et al 2021 ; Xu et al 2021 ). One study suggested that, in temperate regions, warm conditions could promote human thermal comfort (Lin 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The above discussion clarifies the reason for the significant increase in tourist arrivals at hot springs when environmental temperature decreases. From a biological perspective, possible pathways linking exposure to a low-temperature environment with human discomfort may involve organ injuries caused by a decrease in the core body temperature (Min et al 2021 ; Xu et al 2021 ). One study suggested that, in temperate regions, warm conditions could promote human thermal comfort (Lin 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by underweight patients being sensitive to low temperature and in turn achieving poor outcomes. A prior study highlighted that patients with lower BMIs suffered from more cold injury and peripheral vascular disease than patients with higher BMIs due to a shortage of fat tissue [ 20 ]. Furthermore, the results were correlated with the obesity paradox and better outcomes with higher BMIs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Поріг вазоконстрикції у пацієнтів віком від 60 до 80 років нижчий приблизно на 1 o C, ніж у віці 30-50 років [58-61], а тривалість переносимості інтенсивного повітряного охолодження у них в середньому на 36-43 % менше, ніж у молодих випробуваних осіб в аналогічних умовах [48]. Люди похилого віку схильні до підвищеного ризику порушень терморегуляції через зменшення внутрішньосудинного об'єму та зниження серцевої функції [62,63]. За даними епідеміологічних досліджень, близько 50 % смертей у США, що пов'язані з гіпотермією, припадає на людей віком старше 65 років [61].…”
Section: вікові особливостіunclassified
“…Частота обморожень у чоловіків була вищою в усіх вікових групах порівняно з госпіталізованими жінками [64]. Центральна температура у жінок зазвичай знижується швидше, ніж у чоловіків [52,63]. Граничні значення як для потовиділення, так і для вазоконстрикції у представниць жіночої статі на 0,3-0,5 °C вищі, ніж у чоловіків, навіть протягом фолікулярної фази менструального циклу (перші 10 днів).…”
Section: статьunclassified
See 1 more Smart Citation